Effects of cold storage duration on survival rate, growth, and biochemical compositions of diatom Chaetoceros gracilis - พิมลรัตน์ พรพิมล; ศรียะศักดิ์ พัชราวลัย; ดิเรกบุษราคม สถาพร; วุฒิสุทธิเมธาวี สุวิทย์; โชติพันธุ์ ปิยะพงค์ (KKU Science Journal, 2017)
The unicellular marine diatom, Chaetoceros gracilis, has been commonly used as an important live food for crustacean larvae in Thailand. The purpose of this study was to investigate the suitable cold storage duration (chilled temperature at 4-5 degrees Celsius) on viability, growth rate when revived in fresh medium, bacterial variation and biochemical composition of C. gracilis. The results showed that C. gracilis cells were significantly decreased (P<0.05) during chilled storage. After 28 days, cell density and survival rate were shown at 2.29 x 106 cell/milliliter (initial cell 6.67 x 106 cells/milliliter) and 5.08 percentages respectively. The growth rate of C. gracilis, after they were revived in fresh medium, was significantly different (P<0.05) which the cells ,storage for more than three weeks, were unsuitable used for revived in fresh medium since this will affect the quality of samples. The total plate counts and green colony of Vibrio spp. of samples were in the range of 5.64×104 – 2.88×107 and 5.67×103–1.53×107 CFU/milliliter, respectively. Results from this study found that proteins and total lipid ofthe fresh and chilled storage for not more than 7 days of C. gracilis was significantly highest (P<0.05) from that the other groups while the amount of carbohydrate was continuously decreased during chilled storage. These results can be applied for microalgae live feed management for animal larvae cultures.